Pemberdayaan Masyarakat Sekolah melalui Pelatihan Literasi Data dan Infografis dalam Menciptakan Generasi Melek Data - Aswi, Aswi; Poewanto, Bobby; Fakhri, M. Miftach (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This activity aims to improve data literacy competencies so that participants are able to process data and turn it into information, as well as being able to create infographics from the processed data. There were 19 training participants in this activity consisting of 15 students and 4 teachers who taught crafts at Sekolah Menengah Atas Negeri 8 Gowa. The method of this activity consists of 3 main activities, namely the first is online data collection training which aims to find out tools that can help in data collection and how to arrange question items on the instrument. The second main activity is training in simple data processing using various kinds of diagrams available in Microsoft Excel as well as material on descriptive statistics which includes measures of central symptoms and measures of data spread. Finally, the participants were given infographic design training using Canva with the aim of simplifying the results of data processing that was previously carried out into infographics that were more interesting to look at. The results obtained were that the majority of participants felt that there had been great progress from this activity and that this activity was also in accordance with the current competency requirements.